AYAT-AYAT KEBEBASAN BERAGAMA DALAM PERSPEKTIF NASAKH: KAJIAN TERHADAP PENAFSIRAN IBN KATHÎR DAN RASHÎD RIDÂ - Hasan, Moh Abdul Kholiq (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
This article aims to find out how the opinion of IbnKathîr and Rashîd Rid}a about naskh in the Qur?an? How did IbnKathîr and Rashîd Rid}a interpret the verses about religious freedom that were claimed to be annulled? And what are the implications for the interpretation of texts about religious freedom? The research method is a library research, with the object of religious freedom verses claimed to be annulled in the book of IbnKathîr and RashîdRid}â. Using the descriptive-analytical and comparative analysis with Hermeneutics Romansis Friedrich Daniel Ernst Schleiermacher approach, the article argues thatIbnKathîr acknowledges the existence of naskh in the Qur?an, but not everything said as annulled is received by him. While Rashîd Rid}a rejects the theory of naskh in the Qur?an. Related to interpretation, IbnKathîr and Rashîd Rid}a reject the opinion of naskh against the verses of religious freedom. Though Rashîd Rid}a seems more emphatically for his refusal. Being the most important implications are that the verses of religious freedom are fundamental and universal, so it is impossible for them to be annulled; the need for change in the paradigm of the law lapsed; and the creation of a peaceful religious life.